2020
DOI: 10.1364/ol.383171
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-based high-responsivity GeSn short-wave infrared heterojunction phototransistors with a floating base

Abstract: We demonstrate silicon-based p - n - p floating-base GeSn heterojunction phototransistors with enhanced optical responsivity for efficient short-wave infrared (SWIR) photodetection. The narrow-bandgap GeSn active layer sandwiched between the p - G e collector and n - G e base effectively extends the photodetection range in the SWIR range, and the internal gain amplifies the optical response by a factor of more than three a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…However, those characteristics are rather difficult to meet simultaneously within a single device. Most mature GeSn photodetector designs include simple p-i-n diodes in the waveguide-integrated [210,213] and free-space forms [214], MQW p-i-n photodiodes on Si [205,206,215] or Ge-oninsulator [216,217] substrates, p-n-p floating-based heterojunction phototransistors [218,219], pseudomorphic hetero-junction p-i-n diode with resonant cavity [207], and MQW APDs [220,221]. The opto-electrical performances of wavelength-extended Si-Ge photodetectors realizations still do not reach the same levels of Ge devices operating at standard fiber-optic telecommunication windows.…”
Section: Photodiodes Beyond Mainstream Wavebandsmentioning
confidence: 99%
“…However, those characteristics are rather difficult to meet simultaneously within a single device. Most mature GeSn photodetector designs include simple p-i-n diodes in the waveguide-integrated [210,213] and free-space forms [214], MQW p-i-n photodiodes on Si [205,206,215] or Ge-oninsulator [216,217] substrates, p-n-p floating-based heterojunction phototransistors [218,219], pseudomorphic hetero-junction p-i-n diode with resonant cavity [207], and MQW APDs [220,221]. The opto-electrical performances of wavelength-extended Si-Ge photodetectors realizations still do not reach the same levels of Ge devices operating at standard fiber-optic telecommunication windows.…”
Section: Photodiodes Beyond Mainstream Wavebandsmentioning
confidence: 99%
“…Beyond 8% Sn concentration the Ge1-ySny alloy becomes a direct bandgap material [7] and further enhancement of Sn concentration reduces the bandgap and not only increases the absorption coefficient but also shows a red shift [8]. Based on those notable features researchers have developed different types of optical devices such as, light emitting diode [9], LASER [10,11], p-i-n PD [12][13][14][15], metal-semiconductor-metal PD (MSM PD) [16], avalanche photodiode (APD) [17], waveguide PD [18], quantum well infrared photodetector (QWIP) [19][20][21][22] and heterojunction bipolar phototransistor (HPT) [8,[23][24][25][26][27]. Among all those aforesaid PDs, HPT is a potential device.…”
Section: Introductionmentioning
confidence: 99%
“…It is a strong competitor of p-i-n and APD due to its inherent gain and absence of excess noise. A number of researchers have reported the characteristics of HPT based on III-V compounds and their alloys [28][29][30][31][32] and group-IV compounds [23][24][25][26][27]. Basu et al [23] have reported their study on HPT based on GeSn, which shows that GeSn based HPT can compete with InGaAs based devices.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of Sn in Ge not only modifies the electronic band structure by shrinking the direct bandgap and hence red-shifting the absorption edge [ 13 ], but also beyond 8% Sn concentration the GeSn alloy acts as a direct bandgap semiconductor [ 14 ]. This noteworthy feature of GeSn has encouraged researchers to develop different types of optoelectronic devices such as Light Emitting Diodes (LEDs) [ 15 , 16 , 17 ], LASERs [ 18 , 19 , 20 ], Transistor LASERs [ 21 , 22 ], p-i-n PDs [ 23 , 24 , 25 ], quantum well infrared photodetectors (QWIPs) [ 26 , 27 , 28 ], metal-semiconductor-metal photodetectors (MSM PDs) [ 29 , 30 , 31 ], waveguide PDs [ 32 ], and heterojunction bipolar phototransistors (HPTs) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%